Pengaruh Perilaku Konsumtif Penggemar K-POP pada Peluang Usaha dan Pajak Bea Cukai di Indonesia - Riski Febriana (Sahmiyya, 2023)
The purpose of this study is to determine the impact of the consumptive behavior of K-POP fans on business opportunities and customs taxes. This research method uses a literature review approach through journals, theses, and websites regarding the consumptive behavior of K-POP fans on business opportunities and customs taxes. The type used is using qualitative data. namely research used to examine the condition of natural objects. The results of this study are regarding the culture that is currently being discussed, namely Hallyu culture. Hallyu or Korean Wave is a fusion of cultures and a response to the globalization of Asian culture. Consumption behavior is the desire to consume excessively goods that are actually less necessary in order to obtain maximum satisfaction. Currently creative businesses and market places are popping up that make it easier for people to get what they want, including goods from abroad. Fans of the Korean idol group have been known to purchase various versions, citing a desire to collect and take photo cards for fun, even though the songs in each version share the same tracklist. From a business standpoint, many fans who are looking for places to sell KPop merchandise come from students and students such as making photocard decorations, jastip merchandise, mugs, pillows, and others. This K-Pop album tax is a tax imposed on purchases of K-Pop albums originating from Korea. Purchases of products such as albums from Korea include purchases of imported goods that are subject to customs duties.